As contribuições da Revista Brasileira de Educação Especial para o ensino de ciências. - MACENA, Pâmila de Cássia Matos (2023)
This work aims to investigate what has been the focus of scientific productions on science teaching for people with disabilities in the Brazilian Journal of Special Education. It is a qualitative study that addressed the periods of expansion and consolidation of the magazine. Thus, all journal publications from 2005 onwards had their titles analyzed and thus, 20 works were selected. In general, the magazine presented an expansion of the diversity of articles in this area in the last decade and has strongly contemplated the theme that involves the teaching of physics and visual impairment and blindness. It is recommended that other themes can also be strengthened in the journal, such as teaching chemistry, geosciences, environment and sustainability. Throughout this work, it was possible to identify the low academic production on science teaching from an inclusive perspective in the Brazilian Journal of Special Education, taking into account the importance of the theme, which characterizes the need for more work in the area.